ANALISIS EPISTIMOLOGIS DAN PRINSIP-PRINSIP DASAR PEMBENTUKAN HUKUM ISLAM - Putra, Muhammad Yunan (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
Human is to depend on the law; which it created by human self or God’s firmness. The law is understand as the instrument control of human attitude to range between person and others, environment, their leader, nation, and God, even tough the property. In this context, the writer try to analyze the concept of epistemology and principle formulation of Islamic law, those, writer use library approach. Result of analyze shows that, Islamic Law in philosophy subjectively and it resource from value in Islamic concept. Meanwhile, in the side formulation law, Islamic law has the religion habitual in which the judge can take it to policy the problems as the low in social life. In this terms, it based on the theory in Islam such as ; tauhid, judgment, amar makruf nahi mungkar, equal, at-ta’wun, and tolerance. Finally, Islamic Low can be resource of Positive Low which it to policy the problems in social life